ANALISIS KESANTUNAN BERBAHASA PADA NOVEL DUA GARIS BIRU KARYA LUCIA PRIANDARINI - Paulina Juita Doni; Ida Ayu Made Wedasuwari; I Nyoman Adi Susrawan (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
This study aims to determine the form of language politeness and the factory that influence language politeness in the novel “Dua Garis Biru by Lucia Priandarini” . The method used in this study is a qualitative. The data in this study are in the form of the charaters in the novel two Two Blue Lines by Lucia Priandarini. The data source in this research is the novel Two Blue Lines by Lucia Priandarini. The results of this study indcate that there are 41 utterances between the characters on the novel Two Bule Lines by Lucia Priandarini, wich consists of 17 forms of imoerative politeness with the intention of telling, 9 forms of politeness with the intention of giving feedback, 5 forms of telling or declarative politeness, 2 forms of politeness with the intetion of prohibiting, and three forms of politeness with the intention of asking for permission. Factors influencing politeness in language in the novel Two Blue Lines by Lucia Priandarini factors that influence language politeness in Lucia Priandarini, novel Two Blue Lines include word choice factors, kinship, or closeness, factors, status factors and situasional factors.